Innovations in Health Service Delivery : The Corporatization of Public Hospitals - Preker, Alexander S. (Washington, DC: World Bank, 2013)
The question of how best to run our hospitals has been a subject of intense interest for decades with a strong focus over the past 15 years. Hospital care is the largest expenditure category in the health systems of both industrialized and developing countries. Although hospitals play a critical role in ensuring delivery of health services, less is known about how to improve the efficiency and quality of care provided. This book, a well-documented collection of case studies, is an attempt to examine the design, implementation and impact of reforms that introduced market forces in the public hospital sector; and tries to answer three questions: a) what problems did this type of reform try to address; b) what are the core elements of their design, implementation, and evaluation; and c) is there any evidence that this type of reform is successful in addressing problems for which they were intended?. It also provides some insights about recent trends in the reform of public hospitals, with an emphasis on organizational changes such as increased management autonomy, corporatization, and privatization.